PENGARUH MARKET VALUE ADDED, ECONOMIC VALUE ADDED, KEBIJAKAN DIVIDEN DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Syahirah, Cut Sarah; Lautania, Maya Febrianti (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The purpose of this study is to examine the effect of market value added, economic value added, dividend policy and managerial ownership on firm value of manufacturing companies listed in Indonesian Stock Exchange in the period of 2010 to 2014. By using purposive sampling method, from 125 manufacturing companies listed in Indonesian Stock Exchange, 24 manufacturing companies are choosed as the sample in this study.The results of the study show that dependent variable or firm value can be explained by the four of independent variables. Simultaneously the four of independent variables have effect on firm value. Market value added, economic value added, dividend policy, and managerial ownership have significant positive on firm value.Keywords: Market Value Added, Economic Value Added, Dividend Policy, Managerial Ownership, Firm Value